Logo-Antenna Based RFID Tags for Advertising Application - ElMahgoub, Khaled; Elsherbeni, Tamer; Yang, Fan; Elsherbeni, Atef Z.; Sydänheimo, Lauri; Ukkonen, Leena (Applied Computational Electromagnetics Society Journal (ACES), 2010)
In this paper we provide the basis of using radio frequency identification (RFID) tags for advertisement. Two RFID tags that apply to the 866 MHz and 915 MHz operating frequencies, respectively, were designed based on the logos of two universities participating in this project. Several fabrication methods were used to build the RFID tags on different substrates. The experimental results exhibited favorable read ranges and radiation patterns. This work demonstrates the applicapability and design flexibility of RFID tags for many advertising applications.